The Influence of Availability, Channel Operationalization, Ability to Listen, Personal Assistance and Content Quality from Customer Assessment Towards Customer Engagement in Instagram. Case Study: Ghala Floral Design - Ichsan, Miftahul; Rachmawati Chaldun, Evy (Journal of Innovation, Business and Entrepreneurship, 2019)
Abstract. Many businesses have social media right now. Having the customer engagement in social media is therefore an important thing for business to be successful in their social media. The ultimate goal of customer engagement is to retain the customer, to become loyal. Reseacher thus tried to find out from the previous study what influences customer engagement in social media, especially in Instagram. Based on literature reviews and previous research, it is found that the most commonly used parameters to increase customer engagement in Instagram are availability, channel operationalization, customer listening ability, personal assistance, and content quality. This research is conducted on the target market for Ghala Floral Design to help them know what really drives their customer perception to engage with Instagram. Research is conducted through a questionnaire with 200 respondents and analyzed using multiple regression and descriptive analysis, then validated through previous literature and research reviews. The results are that content quality is the most influential factors, followed by channel operationalization, then availability, customer listening, and the least personal assistant. The results of this study can be treated as guidelines and recommendations to Ghala Floral Design to increase their brand engagement through Instagram.Â Keywords: Customer engagement factors, Ghala Floral Design, Instagram, Marketing strategy